Parental activities seeking online parenting support: Is there a digital skill divide? (2016)
ABSTRACT: This study examined the existence of a digital skill divide in Internet use for parenting purposes, exploring whether child-rearing content searched, parental skills on search practices, criteria used in the evaluation of content and satisfaction with the results are modulated by socio-demographic factors and level of Internet experience. Participants were 234 Spanish parents recruited through notices in day care centers, schools and parents’ associations, who reported on these issues through an online survey. Results showed that parents were very active in sear- ching for information on child-rearing issues. However, a digital skill divide can be seen mainly by parental education, gender and age on the content searched and perceived skills for going online. Parental age and education also shaped technical abilities such as searching practices, criteria for evaluating websites (level of confidence and relevance), and satisfaction with search results. In turn, level of experience in Internet use played a more restrictive role confined to searching practices and satisfaction with the results. The present findings may inform initiatives of Internet literacy training applied differentially to help fathers and mothers with low education and Internet experience levels to access higher quality, reliable educational content. They also may provide guidelines for those who develop websites for parents.